Biodegradable Chitosan Dyes for Clean Environment and Their Application as Alternative Green Dyes - Shaimaa H Abdullah (Journal of Global Pharma Technology, 2019)
This research aimed at preparing derivatives of natural polymer Chitosan (CS) carrying chromophoric chromatic groups, such as amine benzaldehyde groups (I, II, III) and aromatic azo dyes (I1-I5), (II1-II5), (III1-III4), which are characterized by their stability till the preparation of environment-friendly biodegradable polymers. The study identified polymers resulting from polymer (CS) interaction with three phenolic benzaldehydes and then the interaction of amine derivatives of these polymers with diazonium salts prepared simultaneously by some aniline in the infrared spectrum FT-IR, proton nuclear magnetic resonance, the X-ray spectrum (X-RD) and the change of physical properties.Keywords: Chitosan, Schiff Base, Azo Dyes, X-Ray, Chitin.